SENDER AND RECEIVER BASED EFFICIENT BROADCASTING ALGORITHM IN MOBILE AD HOC NETWORK (MANET) - Maheswari.R, Uma; B, Chithra. (IJRDO -Journal of Computer Science Engineering, 2016)
In mobile ad hoc networks (MANETs), all the nodes in the network overhear every data transmission occurring in its vicinity and thus, consumes energy unnecessarily. This paper proposed a Novel Broadcast Algorithms for mobile ad hoc networks to improve the effectiveness and afford guarantee for complete delivery of broadcasting. An important objective is to decrease relay redundancy and to evade the broadcast storm difficulty. It proposes two broadcasting algorithms they are, Sender based algorithm and Receiver based algorithm. In this paper we proposed a new Sender based algorithm selects subset of forwarding nodes using 1-hop neighbor information. The proposed algorithms improve the efficiency and also guarantee full delivery.